PENGARUH STRES TERHADAP KINERJA KARYAWAN PT. FEDERAL INTERNATIONAL FINANCE GROUP CABANG KOTA AMBON - Erick Pattiwael; Maria M Tetelepta; Olivia Laura Sahertian (P3M Politeknik Negeri Ambon, 2023)
The current era of economic globalization entailing the enterprising competitiveness prompts every company to rapidly innovate in achieving company goals that might result in an overwhelming pressure upon its workers. In most cases, the employees have undergone the stress at work regardless of their job description that could be perceived as a detrimental element since the performance of an employee would determine the progress of the company per se. Hence, this study is aimed to gauge the effect of stress on employee's performance at PT Federal International Finance Group Ambon Branch. This research is a quantitative research. Collecting data using questionnaires, interviews and observations. The population of this research is the employees of PT Federal International Finance Group Ambon Branch, consisting 46 workers as the sample. Meanwhile, the data analysis technique used for this study is simple linear regression accommodated by SPSS software. The results of this study prove that stress indeed affects employee's working capacity. Employees with high level of stress at work tend to possess a low efficacy level of working performance at PT Federal International Finance Group Ambon Branch. Keywords : Stress, Employee performance, PT. FIFGROUP Cabang Ambon